Education on the Use of BPJS Health for Non-Formal Communities in Perbarakan Village Deli Serdang Regency in 2024 - Sofia Diaz, Aya; Hebron, Okto; Ritonga, Rahmad Ramadhan; Maharani, Putri Sari; Br. Purba, Sri Ulina; Tampubolon, Regina Elianda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
The Social Security Administering Agency (BPJS), which was established on the basis of social justice, benefits, and humanity, is trying to build a program for the Indonesian people called the National Social Security System. In accordance with Law Number 40 of 2004 concerning the National Social Security System, the Social Security Administering Agency (BPJS) was established as a non-profit institution to manage the State's social security program. The community as a whole may not fully understand the implementation of the BPJS program due to the low level of socialization and understanding of the health program. The community has not fully become a BPJS participant, especially those who work in rural areas or as informal laborers (farmers or laborers), because not all of them are registered or have a BPJS card. The purpose of community service is to provide an understanding to the non-formal community regarding the importance of having BPJS Health as a form of affordable and easily accessible health protection, to motivate the non-formal community to join the BPJS health program, and to support increased access for rural communities to quality health services through the use of BPJS health facilities. Community service was carried out in Perbarakan Village, Deli Serdang Regency, with 20 people attending. This activity is effective in empowering the community to access affordable and quality health services through BPJS Kesehatan, although ongoing support is still needed to overcome existing obstacles.